Organization and management of children's education based on school, family and public unity - Eshonqulova Parvina Furqatovna; Hakamov Ulfat Ilhomovich (Genius Publishing Group, 2023)
This article provides information on the organization and management of children's education on the basis of school, family and public unity
Keywords: School; family; society; children